Microorganismos empleados para la biorremediación de efluentes mineros con cianuro - Apaza Aquino, Hugo (2021)
One of the biggest environmental problems is related to mining effluents with cyanide, due to its high degree of toxicity, it causes highly significant impacts on the ecosystem in general. Although there are various technologies for its treatment, bioremediation is a potential alternative because it is friendly to the environment. The main objective is to analyze the main microorganisms used to carry out bioremediation processes of mining effluents with cyanide. A review of the different sources of information on cyanide bioremediation microorganisms was carried out. Finding that a wide diversity of microorganisms that can be used as potential biological agents to bioremedy cyanide are reported, among which those of the genus of Pseudomonas and Bacillus stand out; the main factors that must be taken into account to achieve high efficiencies are pH, temperature, nutrients, biomass concentration and cyanide concentration. Bioremediation using microorganisms is increasingly taking a position to remedy contaminants such as cyanide, but even so in Peru there is a lack of further studies at the pilot and plant level to demonstrate its efficiency, which is achieved at the laboratory level.